PP31 Strategies to manage emergency ambulance telephone callers with sustained high needs – an evaluation using linked data (STRETCHED). Issue 10 (24th September 2019) - Porter, Alison; Edwards, A; Edwards, BM; Evans, BA; Gripper, PC; Hughes, H; John, A; Khanom, A; Petterson, R; Philips, CJ; Scott, J; Tee, A; et al.
Abstract : Background: Ambulance services across the UK have recognised a clinical and operational problem with persistent high users of the 999 service, but there is a lack of evidence about what works in this setting and how. We aim to evaluate the effectiveness, safety and efficiency of multi-agency case management approaches to the care of people who frequently call the emergency ambulance service, and gain understanding of barriers and facilitators to implementation. Methods: We will carry out a mixed methods evaluation using anonymised linked routine data outcomes in a 'natural experiment' cohort design in four UK ambulance services, with one case management intervention site and one control site within each service. We will describe the epidemiology of 'frequent calling'; assess the effects of case management on process, outcomes, safety and costs up to six months for 300 high users per service (n-1200); and examine the views of stakeholders, including patients, through qualitative methods. We will synthesise quantitative and qualitative findings, informed by a logic model describing predicted mechanisms of change. Results: We received confirmation of NIHR grant funding for this study in 2018 so do not yet have results to report. Conclusions: Telephone callers with sustained high needs represent a significant, high profile policy challenge to emergency ambulance services. Such callers may be indicative of gaps elsewhere in the health care system, which could be more effectively addressed by pro-active care. The STRETCHED study provides the opportunity to contribute to the currently sparse evidence base on interventions for this patient group.